EFFECT OF REWARD AND PUNISHMENT ON PERFORMANCE OF EMPLOYEES IN THE ROYAL OF TUNJUNG BALI HOTEL & SPA - Ni Nyoman Ari Novarini; I Gusti Ayu Imbayani (Journal of International Conference Proceedings (JICP), 2019)
The progress of the organization or company can not be separated from the existence of adequate human resources and able to compete. The company is expected to be able to improve the ability of every human resource well so that the company's goals can be achieved. One of them is through the implementation of reward and punishment. Royal Tunjung Bali Hotel & Spa is a business that is engaged in tourism services, realizing that to maximize employee performance, companies must implement a system of reward and punishment. The purpose of this study was to determine the effect of Reward and Punishment on Employee Performance. This study used a population of 35 employees at The Royal Tanjung Bali Hotel & Spa, so that the sample of this study was 35 respondents with census techniques. This study uses multiple linear regression analysis techniques. The results of this study indicate that there is an influence of reward and punishment on employee performance at the Royal Tunjung Bali Hotel & Spa. Suggestions recommended to company management so as to always give praise to employees for the achievement of the resulting performance, so as to improve employee performance, provide severe penalties after proven irregularities by employees without discriminating against the treatment of all employees, employees to be more effective and efficient completion of tasks and work so that the achievement of quantity and reliability of work increases.